1985
DOI: 10.1128/jb.163.1.61-68.1985
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-induced permeabilization of the Escherichia coli outer membrane: comparison of transformation and reconstitution of binding-protein-dependent transport

Abstract: Ca2+ treatment renders the outer membrane of Escherichia coli reversibly permeable for macromolecules. We investigated whether Ca2+-induced uptake of exogenous protein into the periplasm occurs by mechanisms similar to Ca2+-induced uptake of DNA into the cytoplasm during transformation. Protein import through the outer membrane was monitored by measuring reconstitution of maltose transport after the addition of shock fluid containing maltose-binding protein. DNA import through the outer and inner membrane was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In addition to the role of glycine in structural impairment, Kurkdjian et al (1993) reported that glycine acts as an osmoticum and increases the permeability of the membrane. Hence, the addition of glycine to the transformation mixture helps the uptake of exogenous DNA present in the transformation mixture (Bukau et al, 1985). Thus, the increased transformation efficiencies observed in presence of sucrose and glycine, as shown in Table 2, might be due to structural impairments of the bacterial cell wall; furthermore, the osmotic agents might have facilitated DNA uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the role of glycine in structural impairment, Kurkdjian et al (1993) reported that glycine acts as an osmoticum and increases the permeability of the membrane. Hence, the addition of glycine to the transformation mixture helps the uptake of exogenous DNA present in the transformation mixture (Bukau et al, 1985). Thus, the increased transformation efficiencies observed in presence of sucrose and glycine, as shown in Table 2, might be due to structural impairments of the bacterial cell wall; furthermore, the osmotic agents might have facilitated DNA uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of chemical-chemical, chemicalphysical, and physical-physical methods improves the transformation manifolds and is used in laboratories worldwide. Bukau et al (1985) suggested that growth medium supplemented with sucrose facilitates DNA uptake. Transformation efficiency of E. coli may also be enhanced by the use of the simplest amino acid, glycine (1% w/v), in growth medium, as reported by Akhtar et al (1999).…”
Section: Introductionmentioning
confidence: 99%
“…The procedure developed in this report was based upon the ability of certain agents to alter the permeability properties of the outer membrane of gram-negative bacteria. Agents such as calcium ions, chelators, and certain antibiotics and heat or osmotic shock treatments have been used to alter the physical characteristics of the outer membrane (12,33). Molecular mechanisms to explain the loss of the membrane barrier are based upon the disruption of bacterial lipopolysaccharide (25,31,32), as reviewed by Vaara (43), but these explanations remain speculative.…”
mentioning
confidence: 99%